Apoptotic activities of cardenolide glycosides from Asclepias subulata - Rascón-Valenzuela, L. A.; Velázquez, C.; Garibay-Escobar, A.; Vilegas, W. [UNESP]; Medina-Juárez, L. A.; Gámez-Meza, N.; Robles-Zepeda, R. E. (Elsevier, 2016)
Ethnopharmacological relevance Asclepias subulata Decne. (Apocynaceae) is a shrub occurring in Sonora-Arizona desert. The ethnic groups of Sonora, Mexico, Seris and Pimas, use this plant for the treatment of sore eyes, gastrointestinal disorders and cancer. Aim of the study To determine the cell death pathways that the cardenolide glycosides with antiproliferative activity found in the methanol extract of A. subulata are able to activate. Materials and methods The effect of cardenolide glycosides isolated of A. subulata on induction of apoptosis in cancer cells was evaluated through the measuring of several key events of apoptosis. A549 cells were treated for 12 h with doses of 3.0, 0.2, 3.0 and 1.0 µM of 12, 16-dihydroxicalotropin, calotropin, corotoxigenin 3-O-glucopyranoside and desglucouzarin, respectively. Apoptotic and necrotic cell levels were measured by double staining with annexin V-FITC/PI. Mitochondrial membrane depolarization was examined through JC-1 staining. Apoptosis cell death and the apoptosis pathways activated by cardenolide glycosides isolated of A. subulata were further characterized by the measurement of caspase-3, caspase-8 and caspase-9 activity. Results Apoptotic assays showed that the four cardenolide glycosides isolated of A. subulata induced apoptosis in A549 cells, which was evidencing by phosphatidylserine externalization in 18.2%, 17.0%, 23.9% and 22.0% for 12, 16-dihydroxicalotropin, calotropin, corotoxigenin 3-O-glucopyranoside and desglucouzarin, respectively, compared with 4.6% of control cells. Cell death was also associated with a decrease in mitochondrial membrane potential, which was more than 75% in the treated cultures respect to control. The activation of caspase-3 was observed in all cardenolide glycosides-treated cancer cells indicating the caspase-dependent apoptosis of A549 cells. Extrinsic and intrinsic apoptosis pathways were activated by cardenolide glycosides treatment at the doses tested. Conclusion In this study was found that cardenolide glycosides, 12, 16-dihydroxicalotropin, calotropin, corotoxigenin 3-O-glucopyranoside and desglucouzarin, isolated from A. subulata induced the cell death trough caspase-dependent apoptosis, which was activated, preferably, by extrinsic pathway.
Keywords: Apoptosis; Asclepias subulata; Cardenolide glycosides; Caspases